Study on fabrication of ZnO@TiO2 nanocomposite for perozone degradation of amoxicillin from aqueous solution - Thanh Diem Ngo Thi; Xuan Hoan Nguyen; Hiep Vu Phung; Minh Thanh Le; Lan Huong Nguyen (Vietnam Journal of Science, Technology and Engineering, 2023)
In this study, a simple method for fabrication of a ZnO@TiO2 nanocomposite was developed to degrade amoxicillin (AMX) from aqueous solution by heterogeneous photocatalytic perozone under UV irradiation (O3/H2O2/ZnO@TiO2/UV). ZnO nanoparticles were formed by the sol-gel method. The ZnO-NPs were then composited with commercial TiO2 at modification ratios of 0, 10, 20, 30, 40, and 50% of ZnO-NPs to generate ZnO@TiO2 nanocomposites. The physical-chemical characteristics of ZnO, TiO2, and ZnO@TiO2 at the optimal modification ratio were determined using S BET , SEM, EDX, and XRD analysis. The catalytic activity of ZnO@TiO2 was evaluated by degradation of AMX in an O3/H 2O2/ZnO@TiO2/UV system. The results showed that 10%ZnO@TiO2 exhibited the highest catalytic activity in degradation (in term of COD removal) of AMX with about 80% for 70 min of reaction time. This efficiency was higher than that of both systems using ZnO or TiO2 only by double. This primary finding demonstrates the feasibility of 10%ZnO@TiO2 photocatalysts in perozone systems to degrade persistent organic compounds in practical applications.